EFFICACY OF DIFFERENT FORMS OF LOCAL HEMOSTATIC MATERIALS BASED ON OXIDIZE CELLULOSE IN THE EXPERIMENT - A. R. Tarkova; A. M. Chernyavskiy; I. A. Grigor’Ev; S. V. Morozov; V. I. Rodionov; N. I. Kravchenko (Вестник хирургии имени И.И. Грекова)
The bleeding of intraoperative period is one of the actual problem in surgery. There aren’t any universal hemostatic means in spite of large variety of modern hemostatic methods. An experimental research studied the results of hemostatic activity of different forms of materials on the basis of oxidize cellulose (a gauze, a powder) as compared with their foreign analog (a hemostatic gauze «Surgicel»). Median of hemostasis time consisted of (120±59,9) and (73±46,8) s, in case of application of gauze and powder preparations, respectively. The rate of group using the hemostatic gauze «Surgicel» was (142±77,4) s. The authors made a conclusion on the basis of given research, that the hemostatic material based on oxidize cellulose (the powder form) showed a more expressed hemostatic activity and reliably twice reduced the time of hemostasis as compared with their analog forms of gauze (p